2015
DOI: 10.1111/codi.12874
|View full text |Cite
|
Sign up to set email alerts
|

Defining the histopathological changes induced by nonablative radiofrequency treatment of faecal incontinence – a blinded assessment in an animal model

Abstract: In an animal model nonablative RF appeared to induce morphological changes in the IAS and EAS leading to an anatomical state reminiscent of normal sphincter structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
16
0
4
Order By: Relevance
“…It follows a principle that already exists, but applied in a different way. We applied the technique on the urethral meatus after an animal experimental study has demonstrated the possibility of increasing collagen production of anal sphincter ( 9 ) and we used temperatures ranging from 39 to 41°C, as it was proved to be safe and effective in the human genital region ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows a principle that already exists, but applied in a different way. We applied the technique on the urethral meatus after an animal experimental study has demonstrated the possibility of increasing collagen production of anal sphincter ( 9 ) and we used temperatures ranging from 39 to 41°C, as it was proved to be safe and effective in the human genital region ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…A current treatment proposal is the use of radiofrequency, which is a diathermic process generated by the radiation of an electromagnetic spectrum, resulting in an immediate retraction of existing collagen and subsequent activation of fibroblasts causing neocollagenesis ( 9 ). In studies using radiofrequency to treat SUI, a therapeutic response of 50% was shown ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initial assumptions about scarification were erroneous. In contrast to the initial belief that protein denaturation would simply cause scarring and tightening of the tissue, new histologic assessment of tissue treated with RF remodeling revealed that nonablative RF treatment induces morphologic changes in the sphincter complex causing damaged sphincter muscle to become more normal appearing [23]. Numerous other salutary histopathologic and cellular-level structural changes were noted.…”
Section: Radiofrequency Therapymentioning
confidence: 86%
“…In particular, RF energy results in vibration of water molecules and subsequent frictional heating when delivered to a tissue in the frequency range of 200 kHz to 3.3 MHz [ 9 11 ]. Application of SECCA procedure in an animal model appeared to induce morphological changes in the internal and external anal sphincters leading to an anatomical state reminiscent of normal sphincter structure [ 12 ]. Thus, the SECCA procedure provides the release of temperature/impedance controlled RF energy to the sphincteric complex of the anal canal.…”
Section: Introductionmentioning
confidence: 99%